PEMBINAAN KARAKTER MELALUI SHALAT LIMA WAKTU DI MTs NURUL QOLBI PURWAKARTA - A Nasrudin; Sanusi Uwes; Manpan Drajat (Cross-border, 2021)
This study describes character building through five daily prayers at MTs Nurul Qolbi Purwakarta, West Java. The background of the first problem of students ending prayer times. The two prayers are not in congregation. Third, many students do not perform the obligatory prayers on time. The four students lied that they had prayed. Discipline of students arriving late, not doing assignments, not being disciplined in prayer, not being disciplined in obeying school rules and regulations, disciplined in speech and behavior. Character education has not been seen in students. Because in doing prayers and student discipline must be ordered and monitored by the teacher, there has not been an awareness of the students themselves. The purpose of the research is to find out how to implement character building through five daily prayers at MTs Nurul Qolbi. The method used is descriptive method with a qualitative approach. Through interviews, observations and documentation studies. Data comes from interview scripts, field notes, photos, videos, tapes, personal documents, notes or memos, and other official documents through primary and secondary data. Data analysis techniques through data before going to the field, when in the field and processing data. So that conclusions can be drawn. The results of the study show that character building through the five daily prayers can be achieved through habituation, daily school programs, self-awareness of students, exemplary examples from teachers, and teacher monitoring routine evaluations from teachers.